The IFITM protein family in adaptive immunity. Issue 4 (22nd December 2019) - Yánez, Diana C.; Ross, Susan; Crompton, Tessa
Summary: Interferon‐inducible transmembrane (IFITM) proteins are a family of small homologous proteins, localized in the plasma and endolysosomal membranes, which confer cellular resistance to many viruses. In addition, several distinct functions have been associated with different IFITM family members, including germ cell specification (IFITM1–IFITM3), osteoblast function and bone mineralization (IFITM5) and immune functions (IFITM1–3, IFITM6). IFITM1–3 are expressed by T cells and recent experiments have shown that the IFITM proteins are directly involved in adaptive immunity and that they regulate CD4 + T helper cell differentiation in a T‐cell‐intrinsic manner. Here we review the role of the IFITM proteins in T‐cell differentiation and function. Abstract : Recent studies have identified new T‐cell‐intrinsic roles for the IFITM family in T helper differentiation and atopic and inflammatory disease, which are independent of their functions in cellular resistance to viral infection.